MARKETING FOR CULTURE AND THE ARTS: Contributing to the sustainability of nonprofit arts organizations - González Pérez, Gracia María (Abierta. Anuario de investigación, 2015)
This study’s intent is to contribute to the sustainability of all organizations dedicated to the scenic arts, and to help promote their long term growth, basing its analysis in El Salvador’s reality. The document explores the basic issues of said organizations and suggests setting marketing into motion to contribute to their strengthening. Research took place on secondary sources for marketing tools which may be implemented and adapted to El Salvador, based on the information available on the sector as well as the different perspectives of art directors. This work addresses six large areas: culture and arts, audiences, brand identity, the marketing mix for culture and arts, as well as enhancing target audience loyalty and metrics. ECMH ABIERTA_AT_N9-2015-31-38.